Detailed meso-scale simulations of the transient deformation in additively manufactured 316 L stainless steel lattices characterized by phase contrast imaging. (March 2022) - Branch, Brittany A.; Specht, Paul E.; Jensen, Scott; Jared, Bradley
Highlights: In-situ phase contrast imaging of compaction behavior in metallic lattices. Mesoscale simulated radiographs for direct comparison to compression experiments. Simulating shockwave behavior of metallic lattices that includes common build defects. Constitutive parameterization of lattices impacted at supersonic velocities. Abstract: Additive manufacturing (AM) has shifted the industrial paradigm enabling topologically optimized lattice architectures for lightweight structural components that provide superior mechanical properties and energy absorption capabilities. Despite these key advantages, the property-to-performance relationship of AM lattice architectures at high strain rates have not been experimentally characterized, therefore limiting the development of mesoscale modeling techniques to further understand the constitutive response of metallic lattices. Here, we present a methodology to parameterize the constitutive response of AM 316 L stainless steel (SS) lattice architectures through coupling detailed mesoscale simulations that incorporate an as-built lattice characterized by computed tomography (CT) to shock compression experiments coupled to in-situ x-ray phase contrast imaging (PCI). We utilize a structural similarity (SSIM) index to compare PCI images to simulated radiographs generated from the mesoscale simulations to investigate the influence of the constitutive parameters for an octet lattice impacted at 0.60 km/s and 1.26 km/s. These detailed simulations are also compared to mesoscale simulations in idealized lattice architectures to show the importance of incorporating the as-built geometry to make accurate comparisons to experiment. The coupled approach presented offers a more robust method to validate and optimize constitutive properties in AM metal lattices through direct comparison of the transient deformation states. Additionally, the more detailed understanding of dynamic compaction and the primary modes of failure for these complex architectures afforded by this approach facilitates improved design and implementation at application-relevant strain rates. Graphical abstract: Image, graphical abstract